Excel 2007 VBA programmer's reference - Green, John, 1945- (Wrox programmer's references., 2007)
Fully updated and expanded to cover Microsoft Office Excel 2007, this book is aimed at Excel users who want to gain more control over their spreadsheets using VBA or who want to develop Excel applications.; Begins with an overview of VBA, the programming language for the Microsoft Office suite and many other applications, which allows users to do anything from automating Excel tasks to developing full applications with Excel as the development environment.